ANALISIS INTERAKSI ANTARA NILAI EMISI SUKUK DENGAN NILAI EMISI OBLIGASI, NILAI EMISI SAHAM, BI-RATE, IHSG, DAN INFLASI DI INDONESIA 2010:01 â 2013:03 - , NUHBATUL BASYARIAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to analyze the interaction between the value of sukuk (Islamic bonds) at issuance and value of obligation and stock at issuance, Indonesian Composite Index (IHSG), BI rate, and inflation rate in Indonesia. As one of the variables, value of sukuk issue, a product of sharia capital market, will be analyzed for its relation with value of obligation and stock issues as conventional products of capital market, with IHSG as an economic indicator, and with BI-rate and inflation as the money market instrument of Indonesia. The research uses secondary data in the form of value of sukuk at issuance (SUK), value of obligation issue (OBL), value of stock issue (SAH), IHSG, BI-Rate (BIR), and Inflation (INF) in Indonesia during 2010:01-2013:03 period. This research employs VAR-VECM model for analysis. The results of statistical hypothesis tests are as follows: 1) There is a long-term and short-term relationship found between value of sukuk at issuance and value of stock at issuance, IHSG, BI-Rate and inflation, while there is only a short-term relationship found between value of sukuk issue and value of obligation issue 2) In short-term, BI-Rate and inflation variables have dominant and significant impact to the value of sukuk issue. Meanwhile, in long-term, IHSG strongly influences value of sukuk at issuance, followed by BI-rate. The result of Impulse Response Function (IRF) shows positive response of value of sukuk issue resulted from the shocks of value of obligation issue, value of stock issue, and inflation rate. In the other hand, the negative response of value of sukuk issue resulted from the shocks of IHSG and BI-Rate. Based on estimation results of Variance Decomposition (VD) in VECM, the variables which strongly contribute or influence the value of sukuk issue based on order from the strongest to weakest impacts are as follows: the value of sukuk issue itself, inflation rate, value of obligation issue, IHSG, BI-Rate, and value of stock issue.